Assistance of the School Literacy Team (TLS) in the Implementation of the LEKSAM BEDAS Program in Improving Reading and Writing Literacy - Suharyanto H. Soro; Susan Marisan; Khamisah Nurdini; Haldi Rizkiawan Sukarna (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
This community service activity aims to provide assistance to the School Literacy Team to face several challenges, including providing adequate reading materials and resources for students, low interest in reading, and lack of community involvement. The method of implementing community service activities includes mentoring activities, including discussion, training, direct practice and evaluation. The results of the mentoring activities were very effective in motivating TLS LEKSAM BEDAS to complete literacy challenges and improve their reading and writing literacy. This is proven by 1) It has increased the motivation of teachers and students in carrying out School Literacy Movement activities. Apart from that, the increase in participants' knowledge can be seen from the students' activeness in participating in the program from start to finish. 2) Increasing students' knowledge and skills because it is supported by the use of digital book reading sources